The comprehension of figurative language in English literary texts by students for whom English is not a mother tongue - Winberg, Christine (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1994)
This study applies Sperber and Wilson's relevance theory to the comprehension of figurative language in poetry. Students' understanding of metaphor as a linguistic category and comprehension of metaphorical texts are analysed in terms of the principle of relevance. Patterns of comprehension in English first language (Ll) and English second language (ESL) students' analyses of metaphorical texts are discussed and through an analysis of similarities and differences in these patterns of comprehension an attempt is made to develop a pedagogy around relevance theory. Relevance theory's particular emphasis on the role played by "context" in cognition is seen to have significance for the teaching of literature in South African universities. Relevance theory's account of cognition generates a range of educational principles which could be specifically applied to the teaching of metaphor. An appraisal of the strengths and difficulties students experience in expressing their understanding of metaphor in an academic context is included. This was done to further develop relevance theory into a pedagogical approach which takes into account the academic context in which writing occurs. The investigation of the particular difficulties that English metaphor poses for ESL students entailed acquiring a working knowledge of the ways in which metaphor is taught and assessed in DET schools. The interpretations of students of different linguistic, social and educational backgrounds reveal unifying elements that could be incorporated into a pedagogy based on relevance theory. Such a pedagogy would be appropriate to the multilingual/multicultural/multiracial nature of classes in South African universities and would be a more empowering approach to the teaching of English metaphor.
Keywords: English language -- Study and teaching -- Foreign speakers; English literature -- Study and teaching (Higher); Context (Linguistics); Metaphor; Figures of speech